Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a.2^x=128:4=32\)
\(\Rightarrow x=5\)
\(\text{b.(x - 6)3 = (x - 6)2}\)
\(\Rightarrow\hept{\begin{cases}x-6=1\\x-6=0\end{cases}\Rightarrow\hept{\begin{cases}x=7\\x=6\end{cases}}}\)
\(c.x=1;0\)
\(d.\text{ (7x - 11)3 = 25 . 52 + 200}\)
\(\text{ (7x - 11)3 = 1500}\)
\(\text{x là số thập phân}\)
\(\text{e. (2x - 2)3 = 8}\)
\(2x-2=2\)
\(x=2\)
\(\text{f, 3+2x-1 = 24 - [ 42 - ( 22 - 1) ]}\)
\(\text{f, 3+2x-1 =203 }\)
\(2x-1=200\)
\(2x=201\)
\(x=100.5\)
a) \(2^x\cdot4=128\)
\(2^{x+2}=2^7\)
\(x=5\)
b) \(\left(x-6\right)^3=\left(x-6\right)^2\)
\(\left(x-6\right)^3:\left(x-6\right)^2=1\)
\(x-6=1\)
\(x=7\)
c) \(x^{17}=x\)
\(x\in\left\{-1;0;1\right\}\)
d) \(\left(7x-11\right)^3=2^5\cdot5^2+200\)
\(\left(7x-11\right)^3=1000\)
\(7x-11=10\)
\(7x=21\)
\(x=3\)
e) \(\left(2x-2\right)^3=8\)
\(2x-2=2\)
\(2x=4\)
\(x=2\)
f) \(3+2^{x-1}=24-\left[4^2-\left(2^2-1\right)\right]\)
\(3+2^{x-1}=11\)
\(2^{x-1}=8\)
\(x-1=3\)
\(x=4\)
\(2^x.4=128\)
\(\Rightarrow2^x=128:4\)
\(\Rightarrow2^x=32=2^5\)
\(\Rightarrow x=5\)
tíc mình nha
Ta có: A = 1 + 2 + 22 + 23 + 24 + ...... + 2100
=> 2A = 2 + 22 + 23 + 24 + ...... + 2101
=> 2A - A = 2101 - 1
=> A = 2101 - 1
1. 4(x+41)=400
<=>x+41=100
<=>x=59
2.11(x-9)=77
<=>x-9=7
<=>x=16
3.5(x-9)=350
<=>x-9=70
<=>x=79
4.2x-49=3.32
<=>2x=3.32+49
<=>2x=76
<=>x=38
5.200-(2x+6)=43
<=>200-2x-6=64
<=>-2x=64-200+6
<=>-2x=-130
<=>x=65
1) 4(x+41)=400
x+41=400:4
x+41=100
x=100-41
x=59
2) 11(x-9)=77
x-9=77:11
x-9=7
x=7+9
x=16
3) 5(x-9)=350
x-9=350:5
x-9=70
x=70+9
x=79
4) 2x-49=3.3\(^2\)
2x-49=3\(^3\)
2x-49=27
2x=27+49
2x=76
x=76:2
x=38
5, 200-(2x+6)=4\(^3\)
200-(2x+6)=64
2x+6=200-64
2x+6=136
2x=136-6
2x=130
x=130:2
x=65
đúng nha
thanks bn nhìu
\(A=1+5+5^2+..+5^{49}+5^{50}\)
\(5A=5+5^2+5^3+...+5^{50}+5^{51}\)
\(5A-A=\left(5+5^2+5^3+...+5^{51}\right)-\left(1+5+5^2+...+5^{50}\right)\)
\(4A=\left(5-5\right)+\left(5^2-5^2\right)+...+\left(5^{50}+5^{50}\right)+5^{51}-1\)
\(4A=0+0+...+0+5^{51}-1\)
\(4A=5^{51}-1\)
\(A=\frac{5^{51}-1}{4}\)
200-(2x+6)=43
=> 2x+6 = 200 - 64
=> 2x+6 = 136
=> 2x = 136 - 6
=> 2x =130
=> x =65
Vậy x = 65
\(200-\left(2x+6\right)=4^3\)
\(200-\left(2x+6\right)=64\)
\(2x+6=200-64\)
\(2x+6=136\)
\(2x=136-6\)
\(2x=130\)
\(x=130\div2\)
\(x=65\)